Motiv žrtve v dramah Simone Semenič - Hočevar, Mia (Amfiteater (Ljubljana), 2019)
In her plays, Simona Semenič unfolds before us the functional logic of ruling ideologies, which create untouchable positions of power and thus manipulatively construct the position of the victim. An analysis of the dramatic works in the author's opus shows that, with the exception of some texts, the motif of the victim appears in nearly all her dramatic texts, most obviously in: 5boys.si; 1981; the feast or the story of a savoury corpse or how roman abramovič, the character janša, julia kristeva, age 24, simona semenič and the initials z.i. found themselves in a tiny cloud of tobacco smoke (below: the feast); we, the european corpses; sophia or while i almost ask for more or a parable of the ruler and the wisdom (below: sophia); seven cooks, four soldiers, three sophias (below: cooks); and in the performance art pieces i, the victim; do me twice; and the second time. Therefore, the above-mentioned texts were chosen, with regard to the criterion of frequency, for a discussion of the victim motif, in which I have investigated, described, positioned and, above all, classified the diversity of victims in the author's plays. A close reading of the author's texts namely shows that certain victims in her plays are similar to one another. They share common traits or characteristics, through which they may be classified into certain groups or types. It turns out that in the author's texts three (possible) types of victim predominate: the collective, the female, and the specific, conditioned by autobiographical traits: "the victim Simona Semenič". Although Simona Semenič's victims are characters with a name and a clear identity, their character or image can represent not only an individual victim, but also a group or collective one. That is to say, the victim motif is not exclusively bound to one (or more) dramatis personae. This is best exemplified in the works the feast, 1981, 5boys.si and we, the european corpses. In these texts we are faced with a particular victim motif, one not bound to a particular dramatic character; rather, we are dealing with a manifestation of thematic collectivity, that is, the appearance of a larger group of victims within a single character, or within a character (or several characters) which represent(s) a victim of a particular social group (or of society as a whole). This is, typologically speaking, a collective victim. In the texts, the motif of the collective victim appears in various forms. In the works the feast and 1981, we perceive it in the form of multiple persons within one character: in the feast, we are faced, through the confession of a corpse, with countless stories about murdered or abused women from the East, and similarly, in the play 1981, a corpse, appearing alongside a real dead body of someone who died in an accident, represents suicide victims who are closely related to the central characters. All characters within the corpse are clearly named with names and surnames, and although the corpse in 1981 does not function as a dramatic character, one can nevertheless observe in it the appearance of a greater number of victims, who are nonetheless precisely named. A different form of collective victim is to be found in 5boys.si and we, the european corpses, in which one (or several) dramatic character(s) represent(s) a particular social group. In these texts, the collective victim is built literally on the basis of a collectivity - either of a social group or society as a whole. The work 5boys.si uses boys as the main dramatic characters in order to present children as a vulnerable social group, while in we, the european corpses, the collective victim is in fact the whole of society, since all people are victims of the politico-economic machinations of the existing capitalist system. However, Simona Semenič most often puts into the centre of her plays a woman, who either has a central speaking position or whose central place serves to display her social marginality, subjugation or oppression. The author is namely concerned above all with the position of woman (and of her femininity) in patriarchal society, marked by the influences of Catholicism, especially by violence against women and by various sexual stereotypes, such as the persona of the ideal mother. The texts of Simona Semenič often contain images of women who are victims of sexual, psychological and physical violence perpetrated against them by men, as carriers of the dispositive of violence. That is to say, Simona Semenič uses the male-female relationship as the most fundamental relationship with which to depict the relation between the ruler and the ruled and, moreover, she makes use of various stereotyped and fixed intersexual and hierarchical relationships which within society breed the inaudible or silenced voices of the powerless and the subjugated (Pezdirc Bartol). The attitude of society towards women is perhaps called in question most extensively in three works by Simona Semenič which, by their formal and thematic similarity, could be combined into a trilogy: the feast or the story of a savoury corpse or how roman abramovič, the character janša, julia kristeva, age 24, simona semenič and the initials z.i. found themselves in a tiny cloud of tobacco smoke; sophia or while i almost ask for more or a parable of the ruler and the wisdom and seven cooks, four soldiers, three sophias. In these three dramatic works appear abused, humiliated women who have fallen victim to men's senseless atrocities - to wars, as well as other forms of violence and to the Catholic patriarchy as the producer of unjust (sexual and social) hierarchic relations. The motif of the female victim is thus the most frequent victim 54 motif in Simona Semenič's dramatic writing, since through this motif author refers to the suffering of all subjugated, weak and socially marginalised individuals who have been pushed to the margin by the predominantly male ruling nomenclature. In Simona Semenič's opus, a particular place no doubt belongs to her "victim trilogy": i, the victim (2007), do me twice (2009), and the second time (2014). Since 2017, the texts have been united in a genre hybrid work do you hear me?, with which the author opens up a wider field of possibility for unhindered and non-stereotypical questioning of the factors and catalysts of her own writing. The three texts are in themselves a singular autobiography of the author in three plays: they describe, at length and with irony, the history of her diagnoses, her troubles, and other infelicitous occasions, marked by bureaucratic procedure, all of which ensure her the position and status of victimhood. Because she describes her authentic experiences, although in places interwoven with fiction, and because in the texts the dramatis personae are Simona Semenič herself, we have placed the victim motif in her word-solos under the heading "the victim Simona Semenič". The three texts are informed by a bitter critique of the bureaucratic and health care systems, with which the author, as an epileptic, single mother and self-employed person in the field of culture, has to deal with daily. It is through her own experiences that she dissects and analyses the role of women, the underpaid nature of precarious work, the dualism of power and subjugation and, above all, her own position - the position of victimhood, which derives from the system's lack of understanding for her health condition, which is linked to her function as a self-employed artist. The author's frank, sarcastic and even scornful narration about the private sphere is at times discomforting for the reader/viewer, since Simona Semenič stoically discusses topics still stigmatised and tabooed. Her description of intimate and bureaucratic troubles elicits a good measure of sympathy from the readers and viewers and thus closely binds them to the action: the author skilfully uses this to attract them quickly and efficiently. At the same time, by her cynical style she abjures any eventual pity, since with her light-hearted recounting of the advantages of being a "mega victim", she in fact rejects the narrative position of victimhood and abolishes this position, thus withdrawing the initially elicited sympathy from the reader or viewer and unveiling a layer of socio-critical irony.
Keywords: motiv žrtve; postdramatic theatre; postdramsko gledališče; Semenič, Simona; Slovenian drama; slovenska dramatika; victim; žrtev